2018
DOI: 10.12998/wjcc.v6.i13.707
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting the importance of early diagnosis in progressive multi-organ involvement of IgG4-related disease: A case report and review of literature

Abstract: IgG4-related disease (IgG4-RD) is an increasingly recognized pathological entity that tends to involve multiple organs with an elevated level of serum IgG4, which is easily misdiagnosed owing to sharing common clinical features with a variety of other diseases. Here, we report an interesting IgG4-RD case of a woman with progressive multi-organ involvement for over 19 years, started with swollen eyelids, dry eye and mouth, and polydipsia and hydruria. Imaging diagnosis revealed diffuse enlargement of the paroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Although the etiology of IgG4-RD is not clear, it is possibly caused by a genetic, microbiological, or persistent antigenic or autoimmune stimulus [ 19 ]. In addition, several studies demonstrated that IgG4-RD is a Th2-dependent disease [ 1 , 20 ], and it can be a result of immunological and allergic conditions in different organs [ 19 ]. IgG4-RDs include autoimmune pancreatitis, Mikulicz disease (MD), pachymeningitis, hypophysitis, orbital pseudotumor, chronic sclerosing dacryoadenitis, pericarditis, sclerosing cholangitis, prostatitis, and other disorders [ 2 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the etiology of IgG4-RD is not clear, it is possibly caused by a genetic, microbiological, or persistent antigenic or autoimmune stimulus [ 19 ]. In addition, several studies demonstrated that IgG4-RD is a Th2-dependent disease [ 1 , 20 ], and it can be a result of immunological and allergic conditions in different organs [ 19 ]. IgG4-RDs include autoimmune pancreatitis, Mikulicz disease (MD), pachymeningitis, hypophysitis, orbital pseudotumor, chronic sclerosing dacryoadenitis, pericarditis, sclerosing cholangitis, prostatitis, and other disorders [ 2 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among 23 cases, five cases were initially misdiagnosed and only correctly diagnosed after 7–20 months [ 7 , 39 , 42 ]. Xue et al [ 20 ] reported a case of a 60-year-old woman who had been diagnosed as IgG4-RD after 19 years of misdiagnosis. In this period, the patient suffered multi-organ progressive enlargement, involving the parotid glands, lacrimal glands, kidneys, submandibular glands, salivary glands, pituitary, pancreas, and lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More data are required to obtain clarity on the pathophysiology behind IgG4-RD, 6 as well as the lasting effect cryotherapy can inflict on these tumor-like lesions; however, collection of such data will be challenging, as these cases present extremely rarely. We propose that, in exceptional cases with critically compromised airways, when glucocorticoids are contraindicated or no longer control the disease, cryotherapy may become part of a treatment strategy for urgent, long-term, or palliative management.…”
Section: Commentmentioning
confidence: 99%